LEADING INSTRUCTIONAL STRATEGIES FOR TEACHING EFFECTIVE LISTENING TO EFL STUDENTS AT BORNEO TARAKAN UNIVERSITY - Vega, Nofvia De; Gultom, Uli Agustina; Tanjung, Firima Zona (Universitas Borneo Tarakan, 2024)
This paper aims to improve students' listening comprehension by implementing a structured instructional program that emphasizes three critical elements: Listening for Gist, Inferring Meaning, and Detecting Signposts. The primary goal is to identify educational strategies that are effective and can significantly enhance students' academic performance and listening abilities. The study addresses a significant gap in previous research by offering a comprehensive framework that integrates multiple aspects of listening comprehension, thereby contributing to the existing literature. This framework often isolates these skills. The program aims to enhance students' listening scores and cultivate a more profound comprehension of spoken language by implementing a targeted approach. The research utilizes a classroom action research design involving a cohort of 40 students who participated in three distinct instruction cycles. Each cycle focused on A specific listening component, which involved using a combination of active listening techniques, contextual exercises, and signpost identification activities. In order to evaluate the efficacy of the instructional strategies and the progression of the students, pre-and post-test assessments were implemented. In all three cycles, the results show substantial improvements, with average scores increasing from 60 to 75 in Listening for Gist, 65 to 82 in Inferring Meaning, and 70 to 88 in Detecting Signposts. These results indicate that the targeted interventions were effective in improving students' listening skills, as numerous students demonstrated a significant improvement in their ability to understand spoken texts. This research has implications for both educational practice and future research. The results emphasize the significance of a multifaceted approach to listening instruction, which motivates educators to implement comparable frameworks in their instruction. Furthermore, additional research could investigate the long-term implications of these instructional strategies on listening proficiency and their generalisability in various educational settings.